Quantifying the Relationship between the Built Environment Attributes and Urban Sustainability Potentials for Housing Areas - Taher Osman (Buildings, 2016)
The Greater Cairo Metropolitan Region (GCMR) in its seeking to sustainable development (SD) by the year of 2050 facing the serious challenge of around 65 percent of Cairenes live in unplanned settlements. In this respect, the authors examined the effect of urban characteristics of unplanned settlements on SD in the Egyptian context, focusing on the type of unplanned growth on agricultural land. The output of the analysis were fourfold. First of all, we provide a brief overview of previous research on the main types of unplanned settlements in GCMR and the sustainability definition according to the Egyptian context. Secondly, we had a discussion with the local government during our field survey in GCMR to determine the study samples, the main urban characteristics, and the sustainability evaluation criteria in the Egyptian context. Thirdly, through the comparative analysis and geographic information system (GIS), we examined how the character of urban development affected per capita four urban measures in a cross-section of two settlements, one represented the unplanned settlements and other as a comparative planned sample to determine the real gap. Finally, by using the evaluation matrix, the help and block items are estimated for each measure of urban characteristics, providing substantive evidence on how the four measures of urban characteristics have been affected by the urban sprawl.